Comparison of container system residual volumes and the implications for medication error. Issue 4 (26th June 2012) - Lannoy, Damien; Décaudin, Bertrand; von Martius, Konstantin; Odou, Pascal
Abstract : Objectives: Plastic intravenous containers can be categorised as flexible polyvinyl chloride (PVC), flexible non-PVC and semirigid plastic. The characteristics of the container may have an effect on the total volume of fluid delivered, thus impacting the amount of drug a patient receives, but these have been insufficiently studied. This work was an open-label analytical study quantifying the average of the residual volumes for three different types of plastic intravenous containers following infusion under simulated conditions that mimic clinical practice. Methods: A total of 280 containers of three different types (seven different brands) were tested. Containers were also separated according to container volume size (50, 100, 250, 500 and 1000 ml). Each container size was tested 10 times under non-vented conditions. Results: The flexible PVC containers were consistently found to have the lowest mean residual volume of all and were significantly different from the semirigid containers whatever the container size (p<0.05). The flexible non-PVC containers had less residual volume than the semirigid containers for most sizes. Mean residual volumes for the flexible PVC and non-PVC containers were below 5 ml whereas the vast majority of residual volumes for the semirigid containers were above 5 ml. Conclusion: The residual volume after gravity drainage differed significantly from one container type to another. High amounts of residual volume in a container may potentially lead to medication errors by which a patient receives suboptimal therapy due to incomplete administration of the drug. This should be taken into consideration when admixing drugs for intravenous infusion.